2020
DOI: 10.1007/s13224-020-01342-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pregnant Women in Times of Covid-19: A Review of Current Literature

Abstract: Its impact on pregnant women is not yet clear owing to limited data and the knowledge is evolving in several aspects. Based on the available evidences, various clinical guidelines for management of COVID-19 have been formulated. This article intends to compile and summarise guidelines from esteemed organisations, along with their implication in the Indian scenario, and offers an easy tool for clinicians managing pregnant women in times of COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…For suspected COVID pneumonia, computerized tomography (CT scan) is investigation of choice even in pregnancy with minimal risk of radiation exposure to fetus. 23,24 Specific tests include reverse transcriptase-PCR (RT-PCR) on respiratory samples with high sensitivity (95% detection probability). 8,25,26 The US FDA has recently approved rapid molecular PCR-based assay Cepheid's COVID-19 test whose results are available within 45 minutes.…”
Section: Investigationsmentioning
confidence: 99%
See 4 more Smart Citations
“…For suspected COVID pneumonia, computerized tomography (CT scan) is investigation of choice even in pregnancy with minimal risk of radiation exposure to fetus. 23,24 Specific tests include reverse transcriptase-PCR (RT-PCR) on respiratory samples with high sensitivity (95% detection probability). 8,25,26 The US FDA has recently approved rapid molecular PCR-based assay Cepheid's COVID-19 test whose results are available within 45 minutes.…”
Section: Investigationsmentioning
confidence: 99%
“…There is no scientific evidence that COVID-19 increases the risk of fetal congenital malformations or causes miscarriage in early pregnancy and it is definitely not an indication of medical termination of pregnancy. 24,36,37 Some case reports and small studies observed increased complications and adverse maternal and fetal outcome with COVID-19 severe disease. [46][47][48] Royal College of Obstetricians and Gynecologists Guideline has reported some adverse outcome with COVID-19 in pregnancy in the form of slight increased risk of preterm delivery, premature rupture of membranes, maternal sepsis, preeclampsia, and postpartum hemorrhage.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
See 3 more Smart Citations